Personalized drug testing in human pheochromocytoma/paraganglioma primary cultures. Issue 6 (9th May 2022) - Wang, Katharina; Schütze, Ina; Gulde, Sebastian; Bechmann, Nicole; Richter, Susan; Helm, Jana; Lauseker, Michael; Maurer, Julian; Reul, Astrid; Spoettl, Gerald; Klink, Barbara; William, Doreen; et al.
Abstract : Aggressive pheochromocytomas and paragangliomas (PPGLs) are difficult to treat, and molecular targeting is being increasingly considered, but with variable results. This study investigates established and novel molecular-targeted drugs and chemotherapeutic agents for the treatment of PPGLs in human primary cultures and murine cell line spheroids. In PPGLs from 33 patients, including 7 metastatic PPGLs, we identified germline or somatic driver mutations in 79% of cases, allowing us to assess potential differences in drug responsivity between pseudohypoxia-associated cluster 1-related ( n = 10) and kinase signaling-associated cluster 2-related ( n = 14) PPGL primary cultures. Single anti-cancer drugs were either more effective in cluster 1 (cabozantinib, selpercatinib, and 5-FU) or similarly effective in both clusters (everolimus, sunitinib, alpelisib, trametinib, niraparib, entinostat, gemcitabine, AR-A014418, and high-dose zoledronic acid). High-dose estrogen and low-dose zoledronic acid were the only single substances more effective in cluster 2. Neither cluster 1- nor cluster 2-related patient primary cultures responded to HIF-2a inhibitors, temozolomide, dabrafenib, or octreotide. We showed particular efficacy of targeted combination treatments (cabozantinib/everolimus, alpelisib/everolimus, alpelisib/trametinib) in both clusters, with higher efficacy of some targeted combinations in cluster 2 and overall synergistic effects (cabozantinib/everolimus, alpelisib/trametinib) or synergistic effects in cluster 2 (alpelisib/everolimus). Cabozantinib/everolimus combination therapy, gemcitabine, and high-dose zoledronic acid appear to be promising treatment options with particularly high efficacy in SDHB -mutant and metastatic tumors. In conclusion, only minor differences regarding drug responsivity were found between cluster 1 and cluster 2: some single anti-cancer drugs were more effective in cluster 1 and some targeted combination treatments were more effective in cluster 2.